Training as a practice of social and psychological assistance to servicemen mobilized for military service - Andriy Fomenko, (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2016)
The article describes the training as a way of practical assistance to people who mobilized for military service. It revealed some of the features of psychological factors of military society. Presented structural stages of the training in the practice of the space of social and psychological adaptation of military personnel. Described exercises of the interactive game with soldiers in the process of adapting to a new team.
Keywords: training; social interaction; social and psychological adaptation; space social and psychological adjustment; social skills